Mode of antiviral action of silver nanoparticles against HIV-1 - Lara Villegas, Humberto Herman; Ayala Núñez, Nilda Vanesa; Ixtepan Turrent, Liliana del Carmen; Rodríguez Padilla, Cristina (2010)
Background: Silver nanoparticles have proven to exert antiviral activity against HIV-1 at non-cytotoxic concentrations, but the mechanism underlying their HIV-inhibitory activity has not been not fully elucidated. In this study, silver nanoparticles are evaluated to elucidate their mode of antiviral action against HIV-1 using a panel of different in vitro assays. Results: Our data suggest that silver nanoparticles exert anti-HIV activity at an early stage of viral replication, most likely as a virucidal agent or as an inhibitor of viral entry. Silver nanoparticles bind to gp120 in a manner that prevents CD4-dependent virion binding, fusion, and infectivity, acting as an effective virucidal agent against cellfree virus (laboratory strains, clinical isolates, T and M tropic strains, and resistant strains) and cell-associated virus. Besides, silver nanoparticles inhibit post-entry stages of the HIV-1 life cycle. Conclusions: These properties make them a broad-spectrum agent not prone to inducing resistance that could be used preventively against a wide variety of circulating HIV-1 strains.